Identyfikacja i ocena elementów ryzyka współpracy przedsiębiorstw w łańcuchach dostaw - Staniewska Ewa (2022)
In the changing conditions of functioning of economic entities, an important role is played, on the one hand, by identifying resources and areas with the potential to increase competitiveness, and on the other hand, by ensuring the stability as well as safety of processes and reducing uncertainty and risk. Building links between business partners is essential in this respect. The basis for such partnerships in supply chains is cooperation based on trust and risk-sharing. At the same time, it should be emphasized that creating such relationships is not only a challenge, but also an additional source of risk. The purpose of this paper is to identify and assess risk elements occurring in the connections of enterprises in supply chains. Knowledge of risk and potential threats is the basis for creating relationships with partners and building security of enterprises and supply chains. The paper presents the results of research on key elements of risk in the relations of metal industry enterprises operating in supply chains. The research was conducted using a proprietary questionnaire and covered businesses operating in in the metal industry in Poland. The issues examined included such elements as: assessment of the perceived role of monitoring and reducing risk in enterprises, identification of competences in the area of risk analysis and assessment as well as preparation for irregularities and disruptions in supply chains characterized by the studied enterprises, identification of the impact of risk elements in relations with suppliers and recipients on the company's operations, the used risk mitigation methods and factors influencing the implementation of risk management in supply chains. The obtained results allowed to identify the role of the risk of cooperation of enterprises in supply chains and significant factors impacting its reduction. The role of managing relations with business partners as an important element influencing the security of supply chains was also emphasized.